The Translation Forms of First-Person Pronouns in Murder on the Orient Express - Ferisa; Hayatul Cholsy (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2025)
This research aims to describe the translation forms of first-person pronouns used as the subject and object from English into Indonesian. This research is descriptive-comparative with a qualitative approach, which explores the nature of first-person pronouns in two novels. The problem of this research is how the equivalent forms are found in translating first-person pronouns from English into Indonesian in the novel “Murder on the Orients Express”. The results show that there are 155 first-person pronouns in the English novel, indicating that the translation of these pronouns, “I” can be aku, ku- kami, and saya, “me” can be kita and sayalah, “we” can be kereta, kami, and kita, and “us” can be kita and kemari. The differences in translation results are due to the different pronoun systems. English does not have an inclusive and exclusive system for “we”, while Indonesian does not have the first-person pronouns in terms of subjects and objects.